Diagnosis and surgical treatment of a primary splenic torsion in a domestic ferret (Mustela putorius furo). (8th April 2021) - Rooney, T.; Gardhouse, S.; Berke, K.; Cassel, N.; Walsh, T.; Eshar, D.
Abstract : A 4‐year‐old female spayed domestic ferret ( Mustela putorius furo ) presented with a history of vomiting over 24 hours. On physical examination, a significantly enlarged, firm spleen was palpated. Abdominal radiographs and abdominal ultrasound were suggestive of a splenic torsion or splenic infarction. An exploratory laparotomy confirmed the initial diagnosis and splenectomy was performed using a vessel sealing device. Histologic evaluation and culture of the spleen were consistent with primary torsion without evidence of infection or neoplasia. The patient recovered from surgery without complications. Based on a literature search, this is the first report of the clinical diagnosis and successful surgical treatment of a primary splenic torsion in a ferret. Although it appears to be a rare and potentially life‐threatening disease in ferrets, splenic torsion should be considered as a differential diagnosis in ferrets that present with non‐specific signs and a palpably enlarged spleen.